Money monster - Copyright Collection (Library of Congress) (2016)
"Financial TV host Lee Gates and his producer Patty are put in an extreme situation when an irate investor takes over their studio"--Internet movie database WWW site, viewed August 4, 2016.
Sources used: video container; Copyright catalog online; Copyright description; Internet movie database WWW site, viewed August 4, 2016; Wikipedia WWW site, viewed August 4, 2016.
George Clooney, Julia Roberts, Jack O'Connell.
Keywords: Thrillers (Motion pictures); Feature films; Fiction films